2017
DOI: 10.3390/genes8020059
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study to Determine Whether BRCA1 and BRCA2 Mutation Carriers Have Higher Risk of Cardiac Toxicity

Abstract: Anthracycline-based cardiotoxicity is concerning for women with breast cancer and portends a dose-dependent risk of developing left ventricular dysfunction. Overall, the prevalence of heart failure (HF) is ≈2% of the total US population; however, BRCA-deficient mice have shown increased HF. We evaluated for the inherent risk of HF in women with BRCA mutations to determine whether treatment with anthracycline-based therapy increased this risk. We obtained results on BRCA mutation carriers regarding cancer treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Interestingly, these BRCA genes are also involved in preservation of cardiac function, and abnormalities may affect susceptibility to cardiac damage. It has been observed that the presence of either of these gene abnormalities is associated with a higher risk of heart failure in patients receiving anthracycline‐based therapies, irrespective of duration and dosing of anthracycline exposure …”
Section: Shared Risk Factors For Breast Cancer and Cardiovascular Dismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these BRCA genes are also involved in preservation of cardiac function, and abnormalities may affect susceptibility to cardiac damage. It has been observed that the presence of either of these gene abnormalities is associated with a higher risk of heart failure in patients receiving anthracycline‐based therapies, irrespective of duration and dosing of anthracycline exposure …”
Section: Shared Risk Factors For Breast Cancer and Cardiovascular Dismentioning
confidence: 99%
“…It has been observed that the presence of either of these gene abnormalities is associated with a higher risk of heart failure in patients receiving anthracycline-based therapies, irrespective of duration and dosing of anthracycline exposure. 33,34 Breast cancer survivorship has been increasing and comprises the largest group of cancer survivors in the United States. 35 Despite the increased risk of cardiovascular disease in breast cancer survivors, there are no specific guidelines for the assessment and prevention of cardiovascular risk in these patients.…”
Section: Shared Risk Factors For Breast Cancer and Cardiovascular Dmentioning
confidence: 99%
“…Limited by small sample size, the patterns yielded in our study were very obvious, yet not clearly significant, hampered by high variability. Aging is also characterized by increased cardiovascular risk, due to endothelial dysfunction via increased generation of reactive oxygen species (ROS), thus elevating oxidative stress that in turn promotes DNA damage and endothelial cell apoptosis [ 41 ]. It had been recently demonstrated that BRCA mutation carriers had increased risk of chemotherapy-induced cardiotoxicity in both mouse and human [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aging is also characterized by increased cardiovascular risk, due to endothelial dysfunction via increased generation of reactive oxygen species (ROS), thus elevating oxidative stress that in turn promotes DNA damage and endothelial cell apoptosis [ 41 ]. It had been recently demonstrated that BRCA mutation carriers had increased risk of chemotherapy-induced cardiotoxicity in both mouse and human [ 41 , 42 ]. The pre-clinical data obtained in mice highlight an unrecognized role of BRCA as a gatekeeper of inflammation-induced endothelial cell function and a target to limit atherosclerosis [ 43 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies were limited by small sample size and identified no significant SNPs. [11][12][13][14][15][16][17][18][19][20][21][22] Among CGAS that identified significant variants, candidate genes were related to drug metabolism (CBR3, 23 UGT1A6, 24,25 and POR 26 ), drug transport (SLC28A3, 25,27 SLC22A17, 28 SLC22A7, 28 ABCC2, 29 ABCC1, [30][31][32] ABCC5, 33 and ABCG2 34 ), iron metabolism (HFE 29,35 ), cell signalling (RAC2, 29,31 NOS3, 33 and PLCE1 36 ), DNA repair (ERCC2, 37 BRCA1, 38 and BRCA2 38 ), splicing regulation (CELF4 24 ), response to oxidative stress (CAT, 39 NCF4, 31,40,41 GSTP1, 42 and CYBA 31,41 ), calcium homeostasis (ATP2B1 36 ), myosin synthesis (MYH7 43 ), and extracellular matrix synthesis (HAS3 24,44 ). Additionally, two exome array analyses identified candidate genes (ETFB 45 and GPR35 46 ) that were significant only when analysed with a gene-based approach.…”
Section: 1 Anthracyclinesmentioning
confidence: 99%